Zk-SNARKs As A Cryptographic Solution For Data Privacy And Security In The Digital Era - Imam Santoso; Yuli Christyono (International Journal of Mechanical Computational and Manufacturing Research, 2023)
This research brings the concept of zk-SNARKs (Zero-Knowledge Succinct Non-Interactive Argument of Knowledge) in the context of data security and privacy in the digital world. zk-SNARKs is a cryptographic technology that allows individuals to prove a statement or knowledge without having to reveal the actual details of the information. We illustrate this concept through a simple example of proving age over 18 without revealing the actual date of birth. This research highlights the importance of maintaining data privacy in various technological applications, including the use of zk-SNARKs in blockchain to maintain transaction privacy and personal data protection in increasingly sophisticated applications. However, the implementation of zk-SNARKs requires deep mathematical understanding and strong data security concerns. With great potential to support data privacy and security in the evolving digital era, zk-SNARKs is a highly relevant tool in addressing privacy-related challenges in the digital world. The conclusion of this research is that zk-SNARKs is an important tool in maintaining data privacy and security in the digital age. With its ability to allow individuals to prove knowledge or assertions without revealing actual details of information, this technology has wide applications in various sectors, including finance, data management, and data privacy protection. However, it should be emphasized that the implementation of zk-SNARKs requires extra care in securing the system and ensuring that the technology is used properly to maintain high data privacy and security. With further development and understanding in this technology, zk-SNARKs can be an integral component in building a safer and more private digital world.